Brown v. Board of Education : a fight for simple justice - Rubin, Susan Goldman (Holiday House, 2016)
"In 1954, one of the most significant Supreme Court decisions of the twentieth Century aimed to end school segregation in the United States. Although known as Brown v. Board of Education, the ruling applied not just to the case of Linda Carol Brown, an African American third grader refused entry to an all-white Topeka, Kansas school, but to cases involving children in South Carolina, Delaware, Virginia, and Washington, DC"--Dust jacket flap.